2019
DOI: 10.18097/pbmc20196503165
|View full text |Cite
|
Sign up to set email alerts
|

Selenium compounds in redox regulation of inflammation and apoptosis

Abstract: Monocytes and macrophages play a key role in the development of inflammation: under the action of lipopolysaccharides (LPS), absorbed from the intestine, monocytes and macrophages form reactive oxygen species (ROS) and cytokines, this leads to the development of oxidative stress, inflammation and/or apoptosis in all types of tissues. In the cells LPS induce an “internal” TLR4-mediated MAP-kinase inflammatory signaling pathway and cytokines through the superfamily of tumor necrosis factor receptor (TNFR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 125 publications
0
10
0
Order By: Relevance
“…The GPX family have also been reported to be able to stabilize the signaling cascades speed and prevent the vicious circle of oxidative stress and apoptosis. 17 Suzuki et al also found that the expression of GPX2 in rat hepatoma cells was not only related to cell proliferation, but also related to tumor invasion and metastasis . 18 Our previous results coincided with those mentioned in these studies.…”
Section: Discussionmentioning
confidence: 97%
“…The GPX family have also been reported to be able to stabilize the signaling cascades speed and prevent the vicious circle of oxidative stress and apoptosis. 17 Suzuki et al also found that the expression of GPX2 in rat hepatoma cells was not only related to cell proliferation, but also related to tumor invasion and metastasis . 18 Our previous results coincided with those mentioned in these studies.…”
Section: Discussionmentioning
confidence: 97%
“…Various hypotheses have been proposed to explain the apoptosis of macrophages in advanced atherosclerosis, such as deprivation of growth factors or the presence of toxic cytokines (51,52), yet there is no evidence for these hypotheses in vivo. Several studies have pointed out that an increased accumulation of ROS, the product of endoplasmic reticulum stress, activates MAPK, which in turn causes the release of the mitochondrial pro-apoptotic proteins caspase3/7/9, subsequently leading to cell apoptosis (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that ROS induce osteoblast apoptosis, which is bene cial to the generation of osteoclasts [38]. In addition, intracellular ROS must be degraded by antioxidants, such as Cu/Zn SOD, Mn SOD, CAT, GPX, and GR [39]. D7 balances the production of intracellular ROS by increasing the level of antioxidant enzymes, which balances the levels of ROS and antioxidants in the cell to protect it from ROS damage.…”
Section: Discussionmentioning
confidence: 99%